Associations of time spent gardening with mental wellbeing and life satisfaction in mid-to-late adulthood. (May 2023) - Fjaestad, Selma Lunde; Mackelprang, Jessica L.; Sugiyama, Takemi; Chandrabose, Manoj; Owen, Neville; Turrell, Gavin; Kingsley, Jonathan
Abstract: There is relatively limited research investigating the mental health benefits of gardening. In this cross-sectional study, survey data from 4, 919 middle-aged and older adults (46–80 years, 57% women) from Brisbane, Australia, were used to examine the associations of time spent gardening (0, 1–149 or ≥150 min/week) with indicators of mental wellbeing (measured with the Short Warwick-Edinburgh Mental Wellbeing scale) and singe-item measure of life satisfaction. We also investigated whether such associations differed between younger and older age groups (≤63 years and >64 years). Multilevel linear regression models were used to control for individual- and area-level confounders (e.g., gender, neighbourhood disadvantage). Of all participants, 37% reported no gardening, 42% reported gardening for 1–149 min weekly, and 21% reported ≥150 min of weekly gardening. Compared to participants who did not engage in gardening, those who gardened for ≥150 min per week were more likely to report better mental wellbeing (β = 0.64, 95% CI [0.35, 0.93], p < .001; range 7–35) and life satisfaction (β = 0.33, 95% CI [0.18, 0.48], p <. 001; range 1–10). Stratified analyses revealed that these effects were stronger for participants aged 64 years and older. These findings contribute to a burgeoning body of research that indicates gardening may be beneficial for mental health and life satisfaction, that gardening for at least 2.5 hrs per week is linked with better mental health outcomes, and that gardening may be particularly beneficial for older adults. Highlights: Gardening ≥150 min per week was associated with better mental wellbeing. Spending 2.5 hrs gardening weekly was associated with improved life satisfaction. The benefits of gardening were more pronounced for those aged 64 years and older. Gardening may be a public health intervention enhancing population-level wellbeing.